Analisis Kelayakan Fulfilment Center E-commerce Dari Perspektif Penyedia Layanan Logistik - Putri Dwi Annisa; Kurniawan, Wahyu (Metode : Jurnal Teknik Industri, 2024)
The E-commerce market is expected to continue growing until 2025 with an average of 9.6%. All the same, there are several aspects that are pain points in the E-commerce business. Over 90% of customer complaints and negative feedback are related to transit times and late deliveries. 69% of customers are not likely to shop at an E-commerce platform in the future if the purchase is not shipped within two days of the promised date. According to the voice of the customer, it is necessary to have a logistics model to increase the delivery speed at competitive prices. In the E-commerce logistics operation model, the delivery process and fulfillment center activities could be outsourced to logistics service providers. Therefore, this challenge becomes an opportunity for logistics service provider companies. Therefore, a feasibility study analysis of a fulfillment center business is carried out by considering the market aspect, technical aspect, organizational aspect, and financial aspects using case study in Yogyakarta. Based on the four aspects' feasibility analysis, the business fulfillment center is feasible as described from the financial parameters, Net Present Value Rp. 188,020,130, Annual Worth Rp. 24,574,231, Internal Rate of Return 34%, and Benefit Cost Ratio 1.23.